Integration of personal competencies of managers in the business of organizations - Sumrak Vegelj, Tadeja (Dynamic relationships management journal, 2026)
Sustainable awareness and increasing focus on this area has led many researchers to look for ways to best ensure that this mindset is transferred to all stakeholders within the organization. Leaders have the greatest role in this, so their personal competencies are also our main focus of the research. We discuss the recognition of personal competencies defined by other authors through sustainable leadership, the theory of sustainable leadership and competency models, and in the business and sustainability reports of large organizations in Slovenia, we look for the occurrence of recognized personal competencies – ethics, emotional intelligence and personal integrity. The theoretical framework of the research provides some important findings in the field of sustainable management, on the basis of which we carried out a qualitative and quantitative phase and thematically analyzed the business and sustainability reports of large companies in Slovenia and looked for the frequency of occurrence of individual personal competencies. The results provide leaders with insight into the awareness of the competencies that are exposed through the reporting of organizations and in a way set a mirror for them to improve in the field of achieving reporting practices. We found that the awareness of personal competencies is insufficiently shown through business and sustainability reports, which is not yet an indicator of what is the actual awareness of the importance of these competencies in the implementation of sustainable practices. Nevertheless, the research provides some original starting points for further researchers and the basis for conducting in-depth interviews among the heads of larger companies or quantitative research among management bodies.
Keywords: competencies; emotional intelligence; ethics; leadership; personal integrity; sustainability; sustainable leadership